Therapeutic Journey of Pyrazolines as EGFR Tyrosine Kinase Inhibitors: An Insight into Structure-Activity Relationship - Singh, Navdeep; Gupta, Monika (Current Bioactive Compounds, 2020)
Background: Pyrazolines are five-membered heterocycles with two adjacent nitrogen atoms present in the ring and they have attracted many researchers all over the world to assess their potential therapeutic significance. Pyrazolines are known for their crucial role in numerous diseases like cancer via various mechanisms. Pyrazoline and its derivatives have been found to have potent anticancer activity by inhibiting EGFR (Epidermal Growth Factor Receptor Tyrosine Kinase) and other types of RTKs. Rapid advances in the understanding of cellular signaling by EGFR in normal and malignant cells have brought to light the EGFR as a selective anticancer target. The review enlists some recently developed pyrazolines as EGFR tyrosine kinase inhibitor along with their structure-activity relationships. Methods: The structure-activity relationship of different pyrazoline derivatives was discussed along with their epidermal growth factor receptor inhibitory activity. Both review and research articles have been considered and cited in the paper. Results: Pyrazolines have assisted medicinal chemistry by their diverse biological activities which make them a beneficial scaffold. The structure-activity relationship studies on pyrazolines revealed that the structural characteristics and different substitutions on pyrazoline ring alter the EGFR inhibitory activity. Conclusion: In the present review, pyrazoline derivatives with EGFR kinase inhibitory activity are described based on their structure-activity relationships based on their structural substitution pattern around the pyrazoline scaffold.
Keywords: tyrosine kinase